Associations of known and newly identified human milk oligosaccharides with infections in early childhood: the Ulm SPATZ health study - Siziba, Linda P.; Peng, Zhuoxin; Mank, Marko; Stahl, Bernd; Gonsalves, John; Wernecke, Deborah; Rothenbacher, Dietrich; Genuneit, Jon (Frontiers in Immunology, 2025)
IntroductionHuman milk oligosaccharides (HMOs) are bioactive components of breast milk that play a key role in shaping infant immune development and susceptibility to infections. This study investigated associations between 71 known and novel HMOs measured at 6 weeks and 6 months postpartum with infant infections during the first 2 years of life.MethodsA total of 73 HMOs were analyzed in human milk sampled at 6 weeks (n = 144) and 6 months (n = 133) using LC-ESI-IM-qTOF-MS. Infections in infants were assessed using physician-reported questionnaires at 1 and 2 years. Modified Poisson regression was used to assess associations, adjusted for relevant covariates and corrected for multiple testing (FDR < 0.010).ResultsHigher levels of fucosyl(1-3)-iso-lacto-N-octaose, lacto-N-tetraose (LNT), and sialyllacto-N-tetraose b (LSTb) at 6 weeks were associated with higher likelihood of lower respiratory tract infection (LRTI) at 1 year of age. In contrast, elevated difucosyldisialyllacto-N-hexaose-X2 and difucosyl-lacto-N-hexaose II in non-secretor milk were linked to reduced likelihood of otitis media (OM) in the cumulative 2-year period. Higher levels of LNT2 and LSTa in secretor milk at 6 months were associated with a higher likelihood of LRTI in the first and cumulatively up to the second year of life, respectively.ConclusionThese findings suggest that specific HMOs may influence early-life infection susceptibility. However, the associations likely reflect a complex, dynamic balance in human milk composition, potentially driven by early microbial exposures or maternal responses. Further research is needed to clarify whether HMOs directly modulate susceptibility to infection or act through broader immunological pathways.